Penerapan Timeline Challenge Card Sort Dalam Pembelajaran IPS untuk Mengembangkan Berpikir Kronologis dan Keterlibatan Murid - Diana Kholida; Abdul Kodir; Maria Ulfa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Abstract This study examines the effectiveness of the "Timeline Challenge Card Sort" strategy in promoting chronological thinking and student engagement in learning about the Japanese occupation of Indonesia. History instruction should cultivate historical thinking skills and facilitate students' comprehension of historical processes, rather than merely engaging in the memorization of facts. A considerable number of middle school students encounter challenges in arranging historical events in chronological order and exhibit minimal engagement in class. The reliability of the data was ensured through a triangulation of sources and methods. The findings indicate that the incorporation of timeline visualizations and "card-sort" activities into group discussions facilitates students' ability to structure the material, identify chronological sequences, and articulate historical contexts. This pedagogical approach encourages students to conceptualize history as a series of interconnected events rather than as a collection of discrete facts. This approach has been demonstrated to promote behavioral, emotional, and cognitive engagement by fostering active participation, teamwork, and reflective thinking. However, some students still require teacher guidance and carefully crafted questions to develop more sophisticated historical thinking skills beyond a simple chronology. In summary, the "Timeline Challenge Card Sort" has been demonstrated to be a productive method for enhancing chronological thinking skills and fostering a greater interest in history lessons among students.